Pengaruh Efikasi Diri dan Perfeksionisme terhadap Prokrastinasi Akademik dengan Akademik Burnout sebagai Variabel Intervening yang Dilakukan oleh Mahasiswa Prodi Akuntansi Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa Yogyakarta di Masa Perkuliahan Daring - Adia Adi Prabowo; Dewi Kusuma Wardani; Anita Primastiwi (Universitas Negeri Surabaya, 2023)
In today's rapidly changing and highly competitive society, young people suffer from high levels of psychological distress such as anxiety, depression, and panic disorders because of high expectations for their academic performance and maintenance of their abilities. Mental health problems in college graduates are caused by poor academic performance, deteriorating financial circumstances, relationship problems, and loneliness. This research was conducted to determine the effect of self-efficacy and perfectionism on academic procrastination with academic burnout. This type of research uses a quantitative descriptive, purposive sampling technique used to collect a sample of 130 samples conducted at the University of Bachelor of Science, Tamansiswa, Yogyakarta, undergraduate students of the Accounting study program semesters 1, 3 and 7. PLS-SEM analysis is used in this research method, testing PLS analysis. -SEM uses the Outer Model and Inner Model. The results of this study indicate that: the hypothesis of Self-Efficacy, Perfectionism, and Academic Burnout has a positive effect on procrastination. Meanwhile, the variable Self-Efficacy and the variable Perfectionism have no effect on procrastination through academic burnout.